Police Discrimination and Depressive Symptoms in African American Women: The Intergenerational Impact of Genetic and Psychological Factors on Blood Pressure Study (Mary Ann Liebert, 2022)
Introduction: There are significant and pervasive disparities in police violence and discrimination toward African Americans/Blacks. It is possible that these disparities may lead to heightened vulnerability for poor mental health outcomes. The purpose of this study was to ascertain the associations between experiences of police discrimination and depressive symptoms in a community-based sample of African American/Black women. Methods: We performed a cross-sectional multivariable regression analysis using data from the Intergenerational Impact of Genetic and Psychological Factors on Blood Pressure Study that were collected over a 4-year period from September 2015 to June 2019. Depressive symptoms were assessed using 21 items from the Beck Depression Inventory. Police discrimination was assessed by questionnaires ascertaining experiences of discrimination by police; harassment by police or security guards; and experiences of being unfairly stopped, searched, threatened, or abused by police. Results: The analytical sample included 214 participants. Nineteen percent of participants indicated that they believed they experienced harassment from security guards/police due to their race/ethnicity. Fourteen percent of participants indicated that they had been unfairly stopped, searched, questioned, or abused by police. Police harassment was associated with higher depressive symptoms by an average of 4.48 (standard error [SE]=1.35, p<0.001). African American/Black women who were unfairly stopped, searched, or abused by police had higher depressive symptoms by an average of 4.54 (SE=1.57, p<0.01). Conclusion: African American/Black women who experienced police discrimination experienced higher prevalence of depressive symptoms. There is an urgent need for reliable population-level data on police mistreatment and interventions at the individual, community, and societal levels.